FUNGSI SOSIAL KEDAI KOPI BAGI MASYARAKAT KOTA PEKANBARU (STUDI KASUS KEDAI KOPI KIM TENG PEKANBARU) - Ayulestari, Mega; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
A coffee shop is a place that basically provides coffee drinks or other hot drinks. The Coffee Shop Kim Teng Pekanbaru is a legendary coffee shop in the city of Pekanbaru. This study aims to find out how the social functions of coffee shops in the city of Pekanbaru, especially in the Kim Teng Pekanbaru coffee shop. The data of this study were collected through interviews and documentation. Data analysis using qualitative descriptive analysis. From the results of the analysis in this study it can be concluded that coffee shops have socio-economic, political and cultural functions. The main social function of the coffee shop is as a gathering place for people from various groups who use coffee shops as a place to carry out activities to achieve their goals or to fulfill their coffee needs. Furthermore, based on the results of direct observation and observation, the writer can conclude that the issues discussed are work, economic, social, and political issues that are happening in the community.Keywords: Coffee shop, social function